Sistem Informasi Pembayaran Tagihan Hippam Air Kampung Pandu Berbasis Website - Erik Wahyu Saputro; Nira Radita; Bagus Kristomoyo Kristanto (J-INTECH ( Journal of Information and Technology), 2022)
The purpose of this research is to design a bill payment information system for HIPPAM water to make it easier and provide billing information to customers. In designing this website, researchers have conducted research to collect some information by conducting direct observations and conducting interviews with officers who work at HIPPAM water in Pandu Village, which is located on Jalan Ngamarto Gg Pandu Rt 05 Rw 07 Lawang, Lawang District, Malang Regency. This program was created using the Code Igniter framework using the PHP and MySQL programming languages ​​for data storage in the database. In making the website, there are several main stages, namely data collection and analysis, analyzing system requirements, coding and testing. Based on the results of testing to customers and officers, a score of 100% was obtained from 15 respondents who had tested the website. So it can be concluded that the website can operate well and can be well received by residents.